2006
DOI: 10.1002/anie.200600926
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Crystalline Order in 1‐Nonanethiol Monolayers Deposited from Solution

Abstract: Reversible switching between order and disorder in a 1‐nonanethiol selfassembled monolayer (SAM) is easily accomplished by alternately exposing the monolayer to liquid ethanol then to a helium stream (see picture). Upon removing the liquid phase, the development of crystalline order in the monolayer takes place over a time scale of hours, which implies the sequential crystallization of individual thiol domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 46 publications
1
12
2
Order By: Relevance
“…In contrast, the measurements shown in the present work were mostly performed on noncompact alkanethiol monolayers ͓Fig. 53 This leads us to conclude that the medium surrounding the sample plays a key role in the structural and mechanical properties of the alkanethiol monolayers. Regarding the presence of defects, it can be attributed to the surrounding liquid environment, as it was studied in the past by means of infrared techniques: It was concluded that terminal disorder in the alkyl chains was induced by the solvent, in that case of D 2 O, CD 3 OD, and CCl 4 .…”
Section: Folding Mechanismcontrasting
confidence: 57%
“…In contrast, the measurements shown in the present work were mostly performed on noncompact alkanethiol monolayers ͓Fig. 53 This leads us to conclude that the medium surrounding the sample plays a key role in the structural and mechanical properties of the alkanethiol monolayers. Regarding the presence of defects, it can be attributed to the surrounding liquid environment, as it was studied in the past by means of infrared techniques: It was concluded that terminal disorder in the alkyl chains was induced by the solvent, in that case of D 2 O, CD 3 OD, and CCl 4 .…”
Section: Folding Mechanismcontrasting
confidence: 57%
“…Therefore, it is possible to have the S headgroups forming ordered lattices and yet have orientational and conformational disorder in the hydrocarbon chains. 237 Ordered alkanethiolates in SAMs tend to adopt a crystallinelike, all-trans configuration. This issue has been explored by using IR spectroscopy techniques, such as IRRAS and PMIRRAS.…”
Section: Chain Orderingmentioning
confidence: 99%
“…The characterisation of defects of self-assembled monolayers (SAMs) has therefore received considerable attention [10][11][12][13]. Numerous techniques were used for this purpose: scanning tunnelling microscopy (STM) [11,[14][15][16][17][18][19][20][21], infrared spectroscopy, voltammetry [3,6,22], electrochemical impedance spectroscopy (EIS) [3,[23][24][25][26][27][28], X-ray diffraction [29], contact angle measurements [7], scanning electrochemical microscopy (SECM) [30,31].…”
Section: Introductionmentioning
confidence: 99%